Crystal structure of 6,11-dihydro-12H-benzo[e]indeno[1,2-b]oxepin-12-one, C17H12O2 - Wang Yanqing; Liu Hao; Wang Lin; Li Huahao; Dong Lintao (Zeitschrift für Kristallographie - New Crystal Structures)
C17H12O2, monoclinic, P21/c, a = 11.982(2) Å, b = 5.8563(11) Å, c = 17.894(3) Å, β = 99.892(4)°, V = 1237.0(4) Å3, Z = 4, Rgt(F) = 0.0506, wRref(F2) = 0.1221, T = 296.15 K.